2022
DOI: 10.7759/cureus.32136
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Serum Uric Acid Level as an Indicator of Altered Oxidative Balance in Patients With Migraine

Abstract: Introduction: Migraine is one of the most common neurological diseases. The pathophysiology of migraine has not yet been fully elucidated. There is increasing evidence supporting the relationship between oxidative stress and migraine.Method: This is a retrospective, cross-sectional and observational study. The patients were divided into two groups, episodic migraine and chronic migraine. Episodic migraine patients were divided into two subgroups, migraine with aura and migraine without aura. Serum Albumin, tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Yasin et al. found that UA level decreased in migraine patients, and UA was an effective extracellular free radical scavenger 46 . This evidence suggests UA is more likely to play a protective role as an antioxidant agent in the pathogenesis of oxidative stress and orofacial pain.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Yasin et al. found that UA level decreased in migraine patients, and UA was an effective extracellular free radical scavenger 46 . This evidence suggests UA is more likely to play a protective role as an antioxidant agent in the pathogenesis of oxidative stress and orofacial pain.…”
Section: Discussionmentioning
confidence: 98%
“…45 Yasin et al found that UA level decreased in migraine patients, and UA was an effective extracellular free radical scavenger. 46 This evidence suggests UA is more likely to play a protective role as an antioxidant agent in the pathogenesis of oxidative stress and orofacial pain. Recently studies mainly focus on evaluating the effective index of medicine in the treatment of chronic pain through GST levels.…”
Section: Discussionmentioning
confidence: 99%
“…In light of the well-understood etiopathogenesis of gout, with hyperuricemia as a primary intermediary step, attention has been drawn to the repeated observations of a potential link between serum uric acid levels and migraine occurrence [ 23 , 24 , 25 , 26 ]. For instance, a cross-sectional cohort study revealed an exponential relationship between serum urate levels and migraine occurrence when serum urate exceeded 7.8 mg/dL [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest elucidation of the possible relationship between gout and migraine. However, the studies referenced are indeed cross-sectional in nature [ 23 , 24 , 25 , 26 ], and they do not encompass follow-up data [ 27 ]. This underscores the need for further research employing national population cohort data, which includes meticulous demographic matching and long-term follow-up, to replicate and substantiate the potential link observed in these studies.…”
Section: Introductionmentioning
confidence: 99%

Oxidative Stress and Migraine

Jiménez-Jiménez,
Alonso-Navarro,
García-Martín
et al. 2024
Mol Neurobiol